The effect of five day dosing with THCV on THC-induced cognitive, psychological and physiological effects in healthy male human volunteers: A placebo-controlled, double-blind, crossover pilot trial. (February 2016) - Englund, Amir; Atakan, Zerrin; Kralj, Aleksandra; Tunstall, Nigel; Murray, Robin; Morrison, Paul
Rationale: Cannabis is mostly grown under illegal and unregulated circumstances, which seems to favour a product increasingly high in its main cannabinoid ∆-9-tetrahydrocannabinol (THC). ∆-9-tetrahydrocannabivarin (THCV) is a relatively untested cannabinoid which is said to be a cannabinoid receptor neutral antagonist, and may inhibit the effects of THC. Objectives: To explore the safety and tolerability of repeated THCV administration and its effects on symptoms normally induced by THC in a sample of healthy volunteers. Methods: Ten male cannabis users (<25 use occasions) were recruited for this within-subjects, placebo-controlled, double-blind, cross-over pilot study. 10mg oral pure THCV or placebo were administered daily for five days, followed by 1mg intravenous THC on the fifth day. Results: THCV was well tolerated and subjectively indistinguishable from placebo. THC did not significantly increase psychotic symptoms, paranoia or impair short-term memory, while still producing significant intoxicating effects. Delayed verbal recall was impaired by THC and only occurred under placebo condition ( Z =-2.201, p =0.028), suggesting a protective effect of THCV. THCV also inhibited THC-induced increased heart rate ( Z =-2.193, p =0.028). Nine out of ten participants reported THC under THCV condition (compared to placebo) to be subjectively weaker or less intense (χ 2 =6.4, p =0.011). THCV in combination with THC significantly increased memory intrusions ( Z =-2.155, p =0.031). Conclusion: In this first study of THC and THCV, THCV inhibited some of the well-known effects of THC, while potentiating others. These findings need to be interpreted with caution due to a small sample size and lack of THC-induced psychotomimetic and memory-impairing effect, probably owing to the choice of dose.